The responsibilities of Olympic sponsors? BP and the London 2012 Olympic Games - Chard, Chris; Mallen, Cheryl; Bradish, Cheri L. (London : Human Kinetics, Inc., 2013)
In 2008, the London Organising Committee of the Olympic Games (LOCOG) announced that they had signed a $58 million (US) sponsorship agreement with British Petroleum (BP), an oil company with well-known environmental concerns and offenses. The current case is set in July 2010 amidst BP's most recent, and largest, environmental incident. The purpose of this case is to answer a key question: What action (if any) should LOCOG take with respect to its partnership with BP given the Gulf Coast oil spill? Additionally, students are challenged to form opinions regarding the environmental and social responsibilities of an Olympic sponsor, and to develop a strategic plan and policies for Olympic partners related to their environmental and social actions in the future.
Originally published in Chard, C., Mallen, C., & Bradish, C. L. (2013). The responsibilities of Olympic sponsors? BP and the London 2012 Olympic Games. Case Studies in Sport Management, 2(2), 10-16. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; London Organising Committee of the Olympic Games and Paralympic Games; British Petroleum Company; Sports sponsorship; Social responsibility of business